Business process modeling in aquaculture for environmental sustainability and fish traceability: A case study in Italian region. (31st March 2020) - Corallo, Angelo; Latino, Maria Elena; Menegoli, Marta; Cataldo, Marco
Abstract : Aquaculture is an expansion industry and has the potential to satisfy the worldwide demand of fish production related to the global population growth. Technological and methodological innovations are necessary not only to optimize the production but also to assure its sustainability. The paper describes a system to be placed in sea aquaculture plants, in order to improve the enterprise sustainability from environmental, economic and ethical points of view. The system is composed by several devices which work following Internet of Things paradigm, and it is able to solve practical issues emerged from a case study in south of Italy. The data collected by the system, conveniently enriched by other specific information, will be used for traceability purpose, in order to satisfy the market needs of Food Citizenship. The system' devices, the production processes (as‐is and to‐be), the plant maintenance process (as‐is) and the traced data are described. So, the research follow‐ups are discussed.